The Guidelines for Teacher Competencies Development of Zhumadian Preschool Education College in Henan, China - Xin, Chen; Chiwpreecha, Dr. Kesinee (Journal of Dhamma for Life, 2023)
The aims of this research were to study the states and guidelines for teacher competencies development of Zhumadian preschool education college in Henan, China. Using mixed -methods research approach that consisted of 2 steps they were as follows: (1) The quantitative of this study were the population 343 teachers. The statistics used to analyze the data in this study were percentage, mean, standard deviation. (2) Interview 7 experts and analyze data by using content analysis. The results of hypothesis testing are as follows: 1) The teacher competencies development stage of Zhumadian preschool education college in Henan, China is overall at a high level, for the core competency is at a moderate level , while the functional competency is at a high level.2)The guidelines for teacher competencies development are as follows: 1) Core Competency; Working Achievement Motivation development.2) Monitoring and evaluating performance in Working Achievement Motivation development 3) Guideline for Functional Competency; Relationship and Collaborative.